Reduced scald time does not influence ultimate pork quality. (December 2022) - Daniels, R.P.; Wicks, J.C.; Zumbaugh, M.D.; Matarneh, S.K.; Venhuizen, M.D.; Elgin, J.; Bodmer, J.; Yen, C.N.; El-Kadi, S.W.; Shi, H.; Silva, S.L.; Gerrard, D.E.
Abstract: Fresh pork color is a function of pigment, and the pH and temperature conditions in the carcass postmortem. To explore the role of scald on color development, carcasses ( n  = 16) were subjected to either a 4- or 8-min scald. Semimembranosus (SM) muscle samples were collected before and after scalding, and at 24 h postmortem. A 50% reduction in scald time resulted in lighter color (L*) across the muscle early postmortem ( P  < 0.001), yet the 8-min scald treatment was lighter ( P = 0.001 ) at 24 h. An interaction between scald time and sampling time showed in an increase in L* values at 4-min immediately following scald ( P < 0.001 ). Two-hundred carcasses were then subjected to a modified scald time (6.5 min, or 7.5 min) in an industrial setting. Lowering scald time failed to recapitulate results. In fact, darker meat (L* value; P   = 0.0166 ) was noted in the SM across longer scalds. These data suggest modest changes in scald time may not be responsible for changes in pork quality development. Highlights: Reduction of length of scald does not influence muscle temperature. Reduction of scald time does not alleviate color variations in SM. L* value increases immediately following shorter scalds.